Framing Crisis and the Politics of Emotion: How Indonesian Online Media Manage Public Panic in Disaster Reporting - Syarofi, Ahmad; Sholihah, Barokatus (Worldwide Research Publishing, 2026)
Disasters and crises are communication events that not only require the delivery of information but also the management of public emotions. In the context of digital media, news framing plays a crucial role in shaping both public perception and emotional responses to crisis situations. This study aims to analyze how Indonesian online media frame the flash flood crisis in Sumatra and how such framing functions in producing and managing public panic. This research employs a qualitative approach within a critical interpretative paradigm. The object of the study is news coverage of flash floods in Sumatra published by Kompas.com, CNNIndonesia.com, and Detik.com during the period of November 25 to December 31, 2025. Data were analyzed using Entman’s framing analysis model, with a focus on narratives of fear, risk emphasis, and the emotional solutions offered by the media. The findings reveal that online media not only define crises through the emphasis on threats, risks, and urgency, but also actively produce public emotions through dramatic diction, disaster metaphors, and threat visualizations. However, crisis framing also functions as a mechanism for panic management through strategies of normalization, rationalization, and emphasis on the role of authorities and symbolic solutions. These findings indicate that public panic is a media-mediated phenomenon, rather than merely a spontaneous response to disaster events. Theoretically, this study expands the concept of framing by integrating the dimension of the politics of emotion, positioning framing not only as a tool for constructing meaning but also as an instrument for managing public emotions in crisis communication. Practically, this study highlights the importance of strengthening crisis journalism ethics and developing media policies that are more sensitive to the emotional impact of disaster reporting within Indonesia’s digital media ecosystem.